THE ROLE OF TEACHER PERFORMANCE ASSESSMENT (PKG) ON TEACHERS PERFORMANCE AT SMKN 2 JEMBER - Dian Narulita Tristina; Suwignyo Widagdo; Murtadlo Murtadlo (MBA - Journal of Management and Business Aplication, 2018)
The purpose of this researchwasto identify and analyze the aspects of Teacher Performance Assessment (PKG, in Indonesian language is Penilaian Kinerja Guru) on teacher’s performance. The hypothesis of this researchreads the aspects of teacher performance assessment (PKG) partially significant effect on teacher’s performance. The population in this researcharecivil servant teachers of SMKN 2Jember. This research used a Simple Random Samplingtechniquesince the sampling was done randomly without regarding to strata contained in the population and the whole population are teachers of SMKN 2 Jember. The samples in this researchare71civil servant teachers in SMKN 2 Jember. Data collection methods used in this research are observation, interview, questionnaires and documentation. The implications of the findings of this study may contribute to the development of science and for practitioners. The result of this research was to improve the teacher’s performance, then the aspects of PKG should be improved. This was in accordance with the concept of human resources. Some suggestions can be given was the results of this study indicate that aspects of the Teacher Performance Assessment (PKG) gave significant effect on performance partially.